Positive electrode active material powder for lithium secondary battery, its manufacturing method, positive electrode for lithium secondary battery, and lithium secondary battery
By using lithium alloy transition metal oxide to form a positive electrode active material with a single particle or pseudo-single particle structure, the problem of prone electrode active material prone to rupture during production and charging and discharge in the prior art is solved, and higher battery life and safety are achieved.
Patent Information
- Application Number
- JP2024514552
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-09-10
- Filing Date
- 2022-09-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-09-08
AI Technical Summary
Existing lithium-ion battery positive electrode active materials are prone to particle rupture during production and charging and discharging, resulting in a shortened battery life and reduced safety.
Lithium alloy transition metal oxide is used as the positive electrode active material to form a single particle or pseudo-single particle structure, and control it with specific particle size and compaction degree to ensure that the material is not prone to rupture during the manufacturing process.
It effectively reduces the cracking of the positive electrode active material during charging and discharging, improves the high-temperature life and high-temperature storage performance of the battery, and extends the service life of the battery.
Smart Images

Figure 0007662281000003 
Figure 0007662281000004 
Figure 0007662281000005
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0121307 filed on September 10, 2021, and all contents disclosed in the documents of that Korean patent application are incorporated herein by reference.
[0002] The present invention relates to a positive electrode active material powder for a lithium secondary battery, a manufacturing method thereof, a positive electrode for a lithium secondary battery, and a lithium secondary battery, and more particularly to a positive electrode active material powder containing a lithium composite transition metal oxide in the form of a single particle and / or a pseudo-single particle, a positive electrode containing the same, and a lithium secondary battery. [Background technology]
[0003] A lithium secondary battery generally comprises a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode and the negative electrode contain active materials capable of intercalating and deintercalating lithium ions.
[0004] Lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2 or LiMnO4, etc.), lithium iron phosphate compound (LiFePO4), etc. have been used as the positive electrode active material of lithium secondary batteries. Among them, lithium cobalt oxide has the advantage of high operating voltage and excellent capacity characteristics, but the raw material cobalt is expensive and the supply is unstable, making it difficult to commercially apply it to large-capacity batteries. Lithium nickel oxide has low structural stability and is difficult to realize sufficient life characteristics. On the other hand, lithium manganese oxide has excellent stability but has a problem of low capacity characteristics. Therefore, lithium composite transition metal oxides containing two or more transition metals have been developed to compensate for the problems of lithium transition metal oxides containing Ni, Co, or Mn alone, and among them, lithium nickel cobalt manganese oxides containing Ni, Co, and Mn are widely used in the field of electric vehicle batteries.
[0005] Conventional lithium nickel cobalt manganese oxides are generally in the form of spherical secondary particles formed by agglomeration of tens to hundreds of primary particles. However, in the case of lithium nickel cobalt manganese oxides in the form of secondary particles formed by agglomeration of many primary particles, there are problems in that particle cracking occurs easily when the primary particles fall off during the rolling process in the manufacture of the positive electrode, and cracks occur inside the particles during charging and discharging. When particle cracking or cracking occurs in the positive electrode active material, the contact area with the electrolyte increases, and gas generation and degradation of the active material due to side reactions with the electrolyte increase, resulting in a problem of reduced life characteristics.
[0006] Recently, the demand for high-output, high-capacity batteries, such as those for electric vehicles, has been increasing, and so the nickel content in the positive electrode active material has been gradually increasing. When the nickel content in the positive electrode active material is increased, the initial capacity characteristics improve, but when the charge and discharge are repeated, the highly reactive Ni +4 A large amount of ions are generated, causing the structure of the positive electrode active material to collapse, and the rate at which the positive electrode active material degrades increases, resulting in problems such as a decrease in life characteristics and a decrease in battery safety. Summary of the Invention [Problem to be solved by the invention]
[0007] In order to solve the above problems, the present invention aims to provide a positive electrode active material capable of suppressing particle breakage and crack generation during the electrode manufacturing process and the charge / discharge process.
[0008] Another object of the present invention is to provide a positive electrode and a lithium secondary battery that contain the positive electrode active material and thus have improved high-temperature life characteristics, high-temperature storage characteristics, and initial resistance characteristics. [Means for solving the problem]
[0009] In one aspect, the present invention provides a positive electrode active material powder for a lithium secondary battery, which includes a lithium transition metal composite oxide in the form of a single particle consisting of one nodule or a quasi-single particle that is a complex of 30 or less nodules, and satisfies the following formula 1:
[0010] [Formula 1] 0.5≦D mean ×d press / D 50 ≦3 D mean is the average particle size of the nodules of the positive electrode active material powder measured by an electron backscatter diffraction (EBSD) analyzer, and press is a press density value measured after putting 5 g of the positive electrode active material powder into a circular mold having a diameter of 2 cm and applying a pressure of 2000 kgf, and D 50 is a 50% volume cumulative distribution value of the positive electrode active material powder.
[0011] In another aspect, the present invention provides a positive electrode comprising the positive electrode active material powder according to the present invention.
[0012] In still another aspect, the present invention provides a lithium secondary battery comprising the positive electrode according to the present invention. Effect of the Invention
[0013] The positive electrode active material powder for a lithium secondary battery according to the present invention includes a lithium transition metal composite oxide in the form of a single particle and / or a pseudo-single particle having excellent particle strength, and thus particle breakage or cracking caused by rolling during electrode production is reduced. This reduces gas generation and degradation of the positive electrode active material due to side reactions with the electrolyte, thereby enabling the realization of excellent life characteristics and high temperature characteristics.
[0014] In addition, the positive electrode active material powder for a lithium secondary battery according to the present invention satisfies specific conditions for particle size and rolling density, thereby minimizing particle cracking during the electrode manufacturing process and reducing gas generation, and minimizing changes in crystal structure during charging and discharging, resulting in excellent high-temperature life characteristics and high-temperature storage characteristics. [Brief description of the drawings]
[0015] The drawings attached to this specification are illustrative of preferred embodiments of the present invention and serve to facilitate a better understanding of the technical concept of the present invention together with the above-mentioned contents of the invention, and therefore the present invention should not be interpreted as being limited only to the matters described in such drawings. Meanwhile, the shape, size, scale, or proportion of elements in the drawings included in this specification may be exaggerated in order to emphasize a clearer description.
[0016] [Figure 1] 2 is a SEM (Scanning Electron Microscope) photograph of the positive electrode active material powder prepared in Example 1. [Diagram 2] 2 is a SEM photograph of the positive electrode active material powder produced in Comparative Example 1. [Diagram 3] 1 is a graph showing the rate of change in full width at half maximum of (003) peak depending on the SOC (State Of Charge) of a coin cell to which the positive electrode active material powder prepared in Example 1 is applied. [Figure 4] 1 is a graph showing the rate of change in full width at half maximum of (003) peak depending on SOC for the positive electrode active material prepared in Comparative Example 1. [Diagram 5] 1 is a graph showing the change in cell volume when batteries using the positive electrode active materials produced in Examples 1 and 2 and Comparative Examples 1 and 2 are stored at high temperature. [Figure 6] 1 is a graph showing the capacity retention rate versus the number of cycles for batteries including the positive electrode active materials produced in Examples 1 and 2 and Comparative Examples 1 and 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The terms and words used in this specification and the claims should not be interpreted limited to their ordinary and dictionary meanings, but should be interpreted in a way that is consistent with the technical ideas of the present invention, based on the principle that the inventor himself / herself can appropriately define the concepts of terms in order to explain the invention in the best possible way.
[0018] In this specification, terms such as "comprise", "comprise", or "have" are intended to specify the presence of embodied features, numbers, steps, components, or combinations thereof, and should be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, components, or combinations thereof.
[0019] In the present invention, a "single particle" is a particle consisting of one single nodule. In the present invention, a "nodule" refers to a particle unit which may be a single crystal lacking a crystalline grain boundary, or a polycrystal having no apparent grain boundary when observed at a magnification of 5000 to 20000 times using a scanning electron microscope (SEM). In the present invention, a "quasi-single particle" refers to a particle which is a complex formed of 30 or less nodules.
[0020] In the present invention, the term "secondary particle" refers to a particle formed by agglomeration of several tens to several hundreds of primary particles. More specifically, the secondary particle is an agglomeration of 50 or more primary particles.
[0021] The term "particle" as used in the present invention may include any one or all of single particles, quasi-single particles, primary particles, nodules, and secondary particles.
[0022] In the present invention, "D mean" refers to the average particle size of nodules measured by electron backscatter diffraction (EBSD). EBSD analysis was performed by manufacturing an electrode using the positive active material powder to be measured, then cutting the electrode before rolling using ion milling (HITACHI IM-500 accelerating voltage 6 kV) to obtain a cross section, and measuring it with an FE-SEM (JEOL JSM7900F) under the conditions of an accelerating voltage of 15 kV and a WD of 15 mm, with the number of primary particles measured at a scale of approximately 400 ± 10.
[0023] In the present invention, "D 50 " means the particle size at 50% of the volume cumulative particle size distribution of the positive electrode active material powder. 50 can be measured using a laser diffraction method. For example, the positive electrode active material powder is dispersed in a dispersion medium, introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W, and a volume cumulative particle size distribution graph is obtained, and the particle size corresponding to 50% of the volume cumulative amount is obtained and measured.
[0024] In the present invention, "d press " is the press density value of the positive electrode active material powder measured using HPRM-1000. Specifically, after 5 g of the positive electrode active material powder is placed in a cylindrical mold, the mold containing the positive electrode active material powder is pressed with a force of 2000 kgf, and then the height of the pressed mold is measured with a vernier caliper to obtain the press density.
[0025] In the present invention, the "specific surface area" is measured by the BET method, and specifically, can be calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan.
[0026] The present invention will now be described in more detail.
[0027] Cathode active material powder The positive electrode active material powder according to the present invention contains a lithium transition metal composite oxide in the form of a single particle consisting of one nodule or a quasi-single particle which is a composite of 30 or less, preferably 2 to 20, and more preferably 2 to 10 nodules.
[0028] Such a lithium composite transition metal oxide in the form of a single particle and / or pseudo-single particle has higher particle strength than existing lithium composite transition metal oxides in the form of secondary particles in which tens to hundreds of primary particles are aggregated, and therefore is less susceptible to particle cracking during rolling.
[0029] In addition, in the case of the lithium transition metal composite oxide in the form of a single particle or pseudo-single particle according to the present invention, the number of lower-component elements (i.e., nodules) constituting the particle is small, so that the change due to the volume expansion and contraction of the primary particles during charging and discharging is small, and therefore the occurrence of cracks inside the particles is significantly reduced.
[0030] In particular, the inventors of the present invention discovered that when a positive electrode active material powder satisfying the following formula 1 is used, particle cracking during an electrode manufacturing process is minimized, resulting in less gas generation, and changes in crystal structure during charging and discharging are minimized, resulting in improved initial resistance characteristics, high temperature life characteristics, and high temperature storage characteristics.
[0031] [Formula 1] 0.5≦D mean ×d press / D 50 ≦3 D mean is the average particle size of the nodules in the positive electrode active material powder measured by an electron backscatter diffraction (EBSD) analyzer, and press is a press density value measured after putting 5 g of the positive electrode active material powder into a circular mold having a diameter of 2 cm and applying a pressure of 2000 kgf, and D 50 is the 50% volume cumulative distribution value of the positive electrode active material powder.
[0032] D mean×d press / D 50 If the value is less than 0.5, particle cracking becomes severe during rolling of the positive electrode or charging and discharging of the lithium secondary battery, gas generation increases under high temperature conditions, and the life characteristics deteriorate, and the above D mean ×d press / D 50 If the value exceeds 3, the initial resistance of the lithium secondary battery increases. mean ×d press / D 50 may be 0.8 to 3 or 1 to 3.
[0033] On the other hand, the positive electrode active material powder according to the present invention may have a (003) peak full width at half maximum change rate of 25% or less, preferably 20% or less, and more preferably about 3 to 15% during charge and discharge.
[0034] The (003) peak full width at half maximum change rate (unit: %) may be defined by the following formula 2.
[0035] [Formula 2] Rate of change of (003) peak full width at half maximum (%) = [{(003) peak full width at half maximum at SOC.60% - (003) peak full width at half maximum at SOC.0%} / {(003) peak full width at half maximum at SOC.0%}] × 100 The rate of change in the (003) peak full width at half maximum can be measured by an X-ray diffraction method, and specifically, can be measured by the following method.
[0036] After making an electrode from the positive electrode active material powder, it is assembled into an experimental coin cell for operando XRD with a Kapton film window. XRD measurement is performed in transmission mode and 2θ theta scan using Mo target X-ray. 1 st Slit 1 / 4 degree, Soller slit(1 st , 2 nd Both are 0.02 rad, 2 ndThe mask uses 1.68 mm. It is measured at 2θ (theta) of 7 degrees in a 30-degree region at approximately 6 minutes per scan every 0.014 degrees. During the measurement, charge and discharge are advanced at a slow rate of 0.05 C to maintain a state close to equilibrium. After measuring up to 4.25 V, the CV state is maintained for 1 hour, and then discharged to 2.5 V. The full width at half maximum (FWHM) up to 60% of the SOC reference can be analyzed. At this time, the FWHM is a numerical value derived by fitting through the whole pattern (multiple peaks) using only crystal system information instead of the complete structure model, and the split pseudo-Voigt function is used during fitting.
[0037] The fact that the change rate of the full width at half maximum of the (003) peak represented by Formula 2 is as small as 25% or less means that the strain change in the crystal structure of the positive electrode active material is small during charge and discharge. As a result, since the degradation of the positive electrode active material is small, excellent life characteristics can be realized.
[0038] On the other hand, the positive electrode active material according to the present invention may contain a lithium composite transition metal oxide, and specifically, may contain a lithium composite transition metal oxide having a composition as shown in Chemical Formula 1 below.
[0039] [Chemical Formula 1] Li 1+x Ni a Co b M 1 c M 2 d O2 In Chemical Formula 1, M 1 is Mn, Al, or a combination thereof, M 2 is one or more selected from the group consisting of W, Zr, Y, Ba, Ca, Ti, Mg, Ta, and Nb, and 0 ≦ x ≦ 0.5, 0.8 ≦ a < 1, 0 < b < 0.2, 0 < c < 0.2, and 0 ≦ d ≦ 0.05.
[0040] In the chemical formula 1, M 1 is Mn, Al, or a combination thereof, preferably Mn or a combination of Mn and Al. M 2 is one or more selected from the group consisting of Zr, W, Y, Ba, Ca, Ti, Mg, Ta, and Nb, preferably one or more selected from the group consisting of Zr, Y, Mg, and Ti, and more preferably Zr, Y, or a combination thereof. The M 2 element is not necessarily included, but when included in an appropriate amount, it can play a role in promoting grain growth during firing or improving the stability of the crystal structure.
[0041] The 1 + x represents the molar ratio of lithium in the lithium composite transition metal oxide, and may be 0 ≦ x ≦ 0.5, 0 ≦ x ≦ 0.3, or 0 ≦ x ≦ 0.2.
[0042] The a represents the molar ratio of nickel in all the metals excluding lithium in the lithium composite transition metal oxide, and may be 0.8 ≦ a < 1, 0.8 < a ≦ 0.95, or 0.82 ≦ a ≦ 0.95.
[0043] The b represents the molar ratio of cobalt in all the metals excluding lithium in the lithium composite transition metal oxide, and may be 0 < b < 0.2, 0.01 ≦ b < 0.2, or 0.01 ≦ b ≦ 0.15.
[0044] The c represents the molar ratio of M 1 in all the metals excluding lithium in the lithium composite transition metal oxide, and may be 0 < c < 0.2, 0.01 ≦ c < 0.2, or 0.01 ≦ c ≦ 0.15.
[0045] The d represents the molar ratio of the M 2 element in all the metals excluding lithium in the lithium composite transition metal oxide, and may be 0 ≦ d ≦ 0.05, 0 ≦ d ≦ 0.02, or 0 ≦ d ≦ 0.01.
[0046] The positive electrode active material powder according to the present invention has an average nodule particle size D mean Specifically, D mean may be 0.5 μm or more, 1.0 μm or more, or 1.5 μm or more, and D mean The average particle size D of the nodules may be 3.5 μm or less, 3 μm or less, 2.5 μm or less, or 2.0 μm or less. mean If the specific surface area of the positive electrode active material is less than 0.5 μm, the total specific surface area of the positive electrode active material increases, and side reactions with the electrolyte may increase. mean If the particle size exceeds 3.5 μm, the lithium mobility in the positive electrode active material decreases, and the output characteristics of the battery may decrease.
[0047] The positive electrode active material powder according to the present invention has a press density value d measured after placing 5 g of the positive electrode active material powder in a circular mold having a diameter of 2 cm and applying a pressure of 2000 kgf. press The press density of the positive electrode active material powder may be 3 g / cc or more, preferably 3 to 5 g / cc or 3 to 4 g / cc, and more preferably 3 to 3.5 g / cc. When the press density of the positive electrode active material powder satisfies the above range, a high energy density can be achieved.
[0048] The positive electrode active material powder according to the present invention has a 50% cumulative volume distribution value D 50 Specifically, D 50 may be 2 μm or more, 3 μm or more, 4 μm or more, 5 μm or more, 6 μm or more, and may be 10 μm or less, 9 μm or less, 8 μm or less, 7 μm or less. 50 If the specific surface area of the positive electrode active material is less than 2 μm, the total specific surface area of the positive electrode active material increases, and side reactions with the electrolyte may increase. 50 If the thickness exceeds 10 μm, the lithium mobility in the positive electrode active material decreases, and the output characteristics of the battery may decrease.
[0049] Meanwhile, the lithium composite transition metal oxide may further include a coating layer containing one or more coating elements selected from the group consisting of Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb.Mo, Sr, Sb, Bi, Si, and S on the particle surface.
[0050] When a coating layer is present on the surface of the lithium composite transition metal oxide particles, the coating layer suppresses contact between the electrolyte and the lithium composite transition metal oxide, thereby providing the effect of reducing elution of the transition metal and gas generation due to side reactions with the electrolyte.
[0051] Preferably, the coating layer may contain Co as a coating element. When a coating layer containing Co is formed on the surface of a lithium composite transition metal oxide particle in the form of a single particle and / or a pseudo-single particle, it is possible to obtain an effect of suppressing a side reaction with the electrolyte and an effect of improving output.
[0052] On the other hand, the positive electrode active material powder according to the present invention has a BET specific surface area of 0.1 to 1 m 2 / g, preferably 0.3 to 1m 2 / g, more preferably 0.5 to 1m 2 When the BET specific surface area of the positive electrode active material powder satisfies the above range, it is possible to appropriately control side reactions with the electrolyte and at the same time ensure a certain level or more of kinetic mobility of lithium ions at the interface between the positive electrode active material and the electrolyte.
[0053] Method for producing positive electrode active material Next, a method for producing the positive electrode active material powder of the present invention will be described.
[0054] The method for producing a positive electrode active material powder according to the present invention comprises the steps of: (S1) preparing a positive electrode active material powder containing nickel (Ni), cobalt (Co) and M 1(S2) mixing the positive electrode active material precursor and the lithium source material and heat treating the mixture to prepare a positive electrode active material powder.
[0055] The produced positive electrode active material powder contains a lithium transition metal composite oxide in the form of a single particle consisting of one nodule or a quasi-single particle that is a complex of 30 or less nodules, and satisfies the following formula 1.
[0056] [Formula 1] 0.5≦D mean ×d press / D 50 ≦3 D mean is the average grain size of the nodules measured by electron backscatter diffraction (EBSD), and press is a press density value measured after putting 5 g of the positive electrode active material powder into a circular mold having a diameter of 2 cm and applying a pressure of 2000 kgf, and D 50 is a 50% volume cumulative distribution value of the positive electrode active material powder.
[0057] Regarding the formula 1, the above-mentioned contents are similarly applied, so a duplicated explanation will be omitted.
[0058] Each step of the method for producing the positive electrode active material powder will now be described in detail.
[0059] First, nickel (Ni), cobalt (Co) and M 1 For example, the transition metal-containing solution may include a nickel-containing source material, a cobalt-containing source material, a M 1 The M may contain a raw material. 1 The containing source material may be a manganese-containing source material and / or an aluminium-containing source material.
[0060] Thereafter, an ammonium cation-containing complex-forming agent and a basic aqueous solution are added to the transition metal solution to cause a coprecipitation reaction, thereby producing a positive electrode active material precursor.
[0061] The nickel-containing source material may be, for example, a nickel-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specifically may be, but is not limited to, Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, a fatty acid nickel salt, a nickel halide, or a combination thereof.
[0062] The cobalt-containing source material may be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, or oxyhydroxide, and specifically may be, but is not limited to, Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O, or combinations thereof.
[0063] The manganese-containing source material may be, for example, a manganese-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide, oxyhydroxide, or a combination thereof, specifically, a manganese oxide such as Mn2O3, MnO2, Mn3O4, etc.; a manganese salt such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate, manganese citrate, or a manganese fatty acid salt; a manganese oxyhydroxide, a manganese chloride, or a combination thereof, but is not limited thereto.
[0064] The aluminum-containing source material may be, for example, Al2O3, Al(OH)3, Al(NO3)3, Al2(SO4)3, (HO)2AlCH3CO2, HOAl(CH3CO2)2, Al(CH3CO2)3 aluminum halides, or combinations thereof.
[0065] The transition metal-containing solution comprises a nickel-containing source material, a cobalt-containing source material, and M 1 The nickel-containing raw material is added to a solvent, specifically, a mixed solvent of water or an organic solvent (e.g., alcohol, etc.) that is uniformly miscible with water, or an aqueous solution of a nickel-containing raw material, an aqueous solution of a cobalt-containing raw material, and an M 1 The raw materials may be mixed to produce the compound.
[0066] The ammonium cation-containing complexing agent may be, for example, but is not limited to, NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, (NH4)2CO3, or a combination thereof. Meanwhile, the ammonium cation-containing complexing agent may be used in the form of an aqueous solution, and in this case, the solvent may be water or a mixture of water and an organic solvent (specifically, alcohol, etc.) that is uniformly miscible with water.
[0067] The basic compound may be a hydroxide of an alkali metal or an alkaline earth metal, such as NaOH, KOH, or Ca(OH)2, a hydrate thereof, or a combination thereof. The basic compound may also be used in the form of an aqueous solution, and in this case, the solvent may be water or a mixture of water and an organic solvent (specifically, an alcohol, etc.) that is uniformly miscible with water.
[0068] The basic compound is added to adjust the pH of the reaction solution, and may be added in an amount that brings the pH of the metal solution to 8 to 12.
[0069] The co-precipitation reaction may be carried out in an inert atmosphere such as nitrogen or argon at a temperature range of 35°C to 80°C.
[0070] This allows nickel, cobalt, and M 1 It is possible to produce a positive electrode active material precursor containing the cations.
[0071] By the above process, nickel-cobalt-M 1The hydroxide positive electrode active material precursor particles are generated and precipitated in the reaction solution. 1 By adjusting the concentration of the raw materials contained, a positive electrode active material precursor having a nickel (Ni) content of 80 mol % or more, preferably 82 mol % or more, based on the total metal content, can be produced. The precipitated positive electrode active material precursor particles can be separated and dried by a conventional method to produce the positive electrode active material precursor.
[0072] Meanwhile, the positive electrode active material precursor prepared as described above may have a tap density of 2.2 g / cc or less, preferably 1.2 to 2.1 g / cc, and more preferably 1.4 to 2.0 g / cc. When a positive electrode active material precursor having a tap density satisfying the above range is used, it is easy to form a lithium composite transition metal oxide in the form of a single particle and / or a pseudo single particle, and the size of the nodules is appropriately controlled to form a positive electrode active material powder satisfying formula (1). Whether or not single particles and pseudo single particles are formed depends on the process conditions, so when the tap density of the positive electrode active material precursor is out of the above range, a lithium composite transition metal oxide in the desired form may not be formed. When the tap density is out of the above range, an active material in the form of secondary particles may be produced.
[0073] Thereafter, the positive electrode active material precursor and the lithium raw material are mixed and heat-treated.
[0074] The lithium source material may be a lithium-containing sulfate, nitrate, acetate, carbonate, oxalate, citrate, halide, hydroxide, or oxyhydroxide, and is not particularly limited as long as it can be dissolved in water. Specifically, the lithium source material may be Li2CO3, LiNO3, LiNO2, LiOH, LiOH·H2O, LiH, LiF, LiCl, LiBr, LiI, CH3COOLi, Li2O, Li2SO4, CH3COOLi, or Li3C6H5O7, and any one or a mixture of two or more of these may be used.
[0075] The positive electrode active material precursor and the lithium source material may be mixed in a molar ratio of 1:1 to 1.2. The positive electrode active material precursor and the lithium source material may be mixed in a molar ratio of, for example, about 1:1, about 1:1.05, about 1:1.10, about 1:1.15, or about 1:1.20, but are not limited thereto.
[0076] In the case of a high-nickel (High-Ni) NCM-based lithium transition metal composite oxide having a nickel (Ni) content of 80 mol % or more, the heat treatment may be performed at a temperature range of 750°C to 1000°C. The heat treatment may be performed, for example, preferably at a temperature range of 800°C to 925°C, more preferably at a temperature range of 850°C to 910°C. The formation of a positive electrode active material powder in the form of a single particle and / or a pseudo-single particle is affected by the heat treatment temperature condition. Therefore, the D of the positive electrode active material powder produced by performing the heat treatment in the above temperature range is mean ×d press / D 50 The value of D may be between 0.5 and 3.0. As a result, the prepared positive electrode active material may have reduced particle breakage and distortion in the crystal structure during the rolling process or during charging and discharging of a lithium secondary battery including the same, thereby improving the initial resistance characteristics. On the other hand, if the heat treatment temperature is outside the above range, the positive electrode active material powder may be formed as secondary particles rather than single particles and / or pseudo single particles, and D mean ×d press / D 50 The value may not be between 0.5 and 3.0.
[0077] Appropriate heat treatment conditions (i.e., D mean ×d press / D 50 The forming conditions of the positive electrode active material powder having a D value between 0.5 and 3.0 may vary depending on the properties of the positive electrode active material precursor such as the tap density of the precursor, the composition of the components in the precursor, the molar ratio, the presence of additives, etc. For example, when an additive is used during the heat treatment, a single particle / pseudo single particle structure can be obtained even if the heat treatment is performed at a temperature range lower than the above temperature range, and D mean ×d press / D 50The value can satisfy 0.5 to 3.0. The additive may be, for example, Zr, Mg, Sr, Y, etc., and the desired D mean ×d press / D 50 In order to produce a powder having the desired value, the heat treatment temperature can be appropriately adjusted according to the type and content of the additives.
[0078] The heat treatment can be carried out in an air or oxygen atmosphere for, for example, 4 to 12 hours. Specifically, the heat treatment can be carried out for, for example, 4 hours or more, 6 hours or more, 8 hours or more, or 10 hours or more, and can be carried out for 12 hours or less, 10 hours or less, 8 hours or less, or 6 hours or less.
[0079] On the other hand, M 2 When producing a lithium composite transition metal oxide containing a metal, M 2 The metal-containing raw material may be further mixed. 2 The metal-containing raw material is M 2 The metal may be an acetate, carbonate, nitrate, sulfate, halide, sulfide, or oxide.
[0080] Meanwhile, when a coating layer is to be formed on the surface of the lithium composite transition metal oxide, the lithium composite transition metal oxide prepared through the heat treatment may be mixed with a coating raw material, followed by a heat treatment. In this case, the mixing may be solid-phase mixing or liquid-phase mixing, and the heat treatment may be performed at an appropriate temperature depending on the coating raw material. For example, the heat treatment in the coating process may be performed at a temperature in the range of 200°C to 700°C or 300°C to 600°C, but is not limited thereto.
[0081] In addition, it is preferable not to perform a water washing process after the heat treatment when preparing the positive electrode active material powder of the present invention. In the past, when preparing a high-nickel (High-Ni) NCM-based lithium composite transition metal oxide, a water washing process was generally performed after the heat treatment in order to reduce the content of lithium by-products. However, according to the research of the present inventors, it was shown that if a water washing process is performed when preparing a lithium composite transition metal oxide in the form of a single particle and / or a pseudo single particle, the surface characteristics of the lithium composite transition metal oxide are deteriorated and the resistance is increased during the water washing process. Therefore, it is preferable not to perform water washing when preparing the positive electrode active material powder of the present invention, but to consume the residual lithium on the surface of the lithium composite transition metal oxide through the process of forming a coating layer. In this way, when preparing a positive electrode active material without washing the lithium composite transition metal oxide with water, an increase in resistance due to surface defects can be suppressed.
[0082] positive electrode The positive electrode according to the present invention includes the positive electrode active material powder according to the present invention. Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, and the positive electrode active material layer includes the positive electrode active material powder according to the present invention. Since the positive electrode active material powder has been described above, a detailed description thereof will be omitted, and only the remaining components will be described in detail below.
[0083] The positive electrode current collector may include a metal having high conductivity, and is not particularly limited as long as the positive electrode active material layer is easily attached and is non-reactive in the voltage range of the battery. The positive electrode current collector may be, for example, stainless steel, aluminum, nickel, titanium, heat-treated carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may have a thickness of typically 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, the positive electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0084] The positive electrode active material layer may selectively contain a conductive material and a binder, if necessary, in addition to the positive electrode active material powder.
[0085] In this case, the positive electrode active material powder may be included in an amount of 80 to 99 wt %, more specifically, 85 to 98.5 wt %, based on the total weight of the positive electrode active material layer. When included in this range, excellent capacity characteristics can be exhibited.
[0086] The conductive material is used to impart conductivity to the electrode, and can be used without any particular restrictions as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive tubes such as carbon nanotubes; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.
[0087] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector.Specific examples of the binder include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylalcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and polymers in which hydrogen is substituted with Li, Na, or Ca, or various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.
[0088] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material powder. Specifically, the positive electrode may be manufactured by applying a positive electrode slurry composition prepared by dissolving or dispersing the positive electrode active material powder and, optionally, a binder, a conductive material, and a dispersant in a solvent onto a positive electrode current collector, followed by drying and rolling.
[0089] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), dimethyl formamide (DMF), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, binder, and dispersant in consideration of the coating thickness of the slurry and the manufacturing yield, and to have a viscosity that can show excellent thickness uniformity when applied to manufacture a positive electrode.
[0090] Alternatively, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the composition from the support, and laminating the resulting film on a positive electrode current collector.
[0091] Electrochemical Devices Next, an electrochemical device according to the present invention will be described. The electrochemical device according to the present invention includes the above-mentioned positive electrode of the present invention, and the electrochemical device may be, specifically, a battery, a capacitor, or the like, and more specifically, a lithium secondary battery.
[0092] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Since the positive electrode is as described above, detailed description thereof will be omitted, and only the remaining components will be described in detail below.
[0093] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly including the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.
[0094] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0095] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, heat-treated carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and may have fine irregularities formed on the surface of the current collector to strengthen the binding force of the negative electrode active material, as in the case of the positive electrode current collector. For example, the negative electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.
[0096] The negative electrode active material layer includes a negative electrode active material and, optionally, a binder and a conductive material.
[0097] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a metallic lithium thin film may be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon may be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, scaly, spherical or fibrous natural graphite, artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature heat-treated carbon such as petroleum or coal tar pitch derived cokes.
[0098] The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.
[0099] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and is usually added in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), nitrile-butadiene rubber, fluororubber, and various copolymers thereof.
[0100] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0101] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material and, optionally, a binder and a conductive material in a solvent on a negative electrode current collector and drying the coating. Alternatively, the negative electrode slurry composition may be cast on a separate support, and then peeled off from the support to obtain a film, which may be laminated on the negative electrode current collector.
[0102] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitations. In particular, a separator having low resistance to ion movement of the electrolyte and excellent electrolyte impregnation ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric material may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.
[0103] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.
[0104] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0105] The organic solvent may be any solvent that can move ions involved in the electrochemical reaction of the battery without any particular limitation. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvent that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant capable of enhancing the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred.
[0106] The lithium salt can be used without any particular limitation as long as it is a compound that can provide lithium ions used in a lithium secondary battery. Specifically, the anion of the lithium salt is F- , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - The lithium salt may be at least one selected from the group consisting of LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The lithium salt is preferably used in a concentration range of 0.1M to 2.0M. When the lithium salt concentration is within the above range, the electrolyte has appropriate conductivity and viscosity, so that excellent electrolyte performance can be exhibited and lithium ions can be effectively transferred.
[0107] In addition to the components of the electrolyte, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 wt % based on the total weight of the electrolyte.
[0108] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and is not limited to the embodiments set forth herein.
[0109] Example 1 After 4L of distilled water was put into a 20L coprecipitation reactor, the temperature was maintained at 50℃, and a 3.2mol / L transition metal solution, which was a mixture of NiSO4, CoSO4, and MnSO4 with a molar ratio of nickel:cobalt:manganese of 0.83:0.11:0.06, was continuously fed into the reactor at 300mL / hr, and a 28wt% aqueous ammonia solution was continuously fed into the reactor at 42mL / hr. The impeller stirring speed was set at 400rpm, and a 40wt% sodium hydroxide solution was added to maintain the pH at 9.3. The mixture was then co-precipitated for 10 hours to form precursor particles, which were then separated, washed, and dried in an oven at 130℃ to produce a precursor (tap density: 1.8g / cc).
[0110] Ni synthesized by coprecipitation reaction 0.83 Co 0.11 Mn 0.06The (OH)2 precursor was mixed with LiOH so that the Li / Me(Ni+Co+Mn) molar ratio was 1.05, and the mixture was heat-treated at 870°C in an oxygen atmosphere for 10 hours to obtain LiNi 0.83 Co 0.11 Mn 0.06 A positive electrode active material powder having the O2 composition was produced. Figure 1 shows an SEM image of the produced positive electrode active material powder.
[0111] Example 2 Ni 0.83 Co 0.11 Mn 0.06 A positive electrode active material powder was produced in the same manner as in Example 1, except that the (OH)2 precursor was mixed with LiOH so that the Li / Me(Ni, Co, Mn) molar ratio was 1.05, and the mixture was heat-treated at 900°C in an oxygen atmosphere for 10 hours.
[0112] Comparative Example 1 Ni 0.83 Co 0.11 Mn 0.06 A positive electrode active material powder was produced in the same manner as in Example 1, except that the (OH)2 precursor was mixed with LiOH so that the Li / Me(Ni, Co, Mn) molar ratio was 1.05, and heat-treated at 780°C in an oxygen atmosphere for 10 hours. A SEM photograph of the produced positive electrode active material powder is shown in Figure 2.
[0113] Comparative Example 2 Ni 0.83 Co 0.11 Mn 0.06 A positive electrode active material powder was produced in the same manner as in Example 1, except that the (OH)2 precursor was mixed with LiOH so that the Li / Me(Ni, Co, Mn) molar ratio was 1.05, and the mixture was heat-treated at 950°C in an oxygen atmosphere for 10 hours.
[0114] Experimental Example 1 For the positive electrode active material powders produced in Examples 1 and 2 and Comparative Examples 1 and 2, mean , d press , D 50 Measure the value and D mean ×d press / D 50 values were calculated.
[0115] D mean is the average grain size of the nodules measured by electron backscatter diffraction (EBSD), and D press is the press density value measured when 5 g of the positive electrode active material powder is placed in a circular mold with a diameter of 2 cm and rolled at 2000 kgf, and D 50 used the 50% volume cumulative distribution value measured by laser diffraction method.
[0116] [Table 1]
[0117] In the case of Examples 1 and 2, 0.5≦D mean ×d press / D 50 ≦3, while in the case of Comparative Example 1, D mean ×d press / D 50 In the case of Comparative Example 2, the value is less than 0.5. mean ×d press / D 50 You can see that the value is greater than 3.
[0118] Experimental Example 2 For the positive electrode active material powders prepared in Example 1 and Comparative Example 1, the (003) peak full width at half maximum was measured by X-ray diffraction (XRD) in the following manner, and the (003) peak full width at half maximum change rate was calculated using the measured values.
[0119] First, a coin cell containing the positive electrode active material powder was manufactured. The coin cell was manufactured as an operando XRD coin cell with a Kapton film window for XRD analysis. Then, the coin cell was charged and discharged while measuring in-situ XRD in transmission mode. Mo target X-ray was used as a light source for XRD measurement, and measurements were performed in a 2θ scan mode in transmission mode. 1st The slit is 1 / 4 degree, Soller slit (1 st , 2 nd Both) are 0.02 rad, 2 nd A mask with a thickness of 1.68 mm was used. Measurements were taken in the 2-θ7° to 30° range at intervals of 0.014° for approximately 6 minutes per scan. Charge and discharge were performed at 0.05C during the measurements, and after measuring up to 4.25V, the CV state was maintained for 1 hour, and then the device was discharged down to 2.5V. A high-energy XRD Empyrean was used as the measurement equipment.
[0120] The rate of change in the full width at half maximum of the (003) peak was calculated as [{full width at half maximum of the (003) peak at SOC.60% - full width at half maximum of the (003) peak at SOC.0%} / {full width at half maximum of the (003) peak at SOC.0%}] × 100.
[0121] The measurement results are shown in Figures 3 and 4. Figure 3 is a diagram showing the full width at half maximum change rate depending on SOC for the positive electrode active material powder of Example 1, and Figure 4 is a diagram showing the full width at half maximum change rate depending on SOC for the positive electrode active material powder of Comparative Example 1.
[0122] 3 and 4, it is confirmed that the full width at half maximum change rate of the (003) peak is 15% or less in Example 1, and the full width at half maximum change rate of the (003) peak is more than 60% in Comparative Example 1. As a result, it is confirmed that there is almost no change in the crystal size and distortion in the structure even when Example 1 is charged at SOC.60% or discharged at SOC.0%, and that particle cracking and stress on the crystal structure during charging and discharging are reduced.
[0123] Experimental Example 3 Coin half cells containing the positive active material powders of Examples 1-2 and Comparative Examples 1-2 were manufactured and charged at 4.25V. Then, two electrodes (loading amount: 400mg) charged at 4.25V and one separator were placed on the lower plate of the coin cell and fixed with a gasket, and 15ul of electrolyte (DEC REF.) was vacuum-injected twice, and each side was vacuum-sealed to a thickness of 1cm using an aluminum pouch with a size of 6.5x5cm. Here, the vacuum sealing means that the cells were sealed under mono-cell vacuum sealing conditions of 95kPa / 93kPa. The coin half cells manufactured as described above were then stored in a convection oven at 60°C for 8 weeks, and the gas generation amount was evaluated by comparing the change in cell volume, and the results are shown in FIG. 5.
[0124] 5, in the case of the cells using the positive electrode active material powders according to Examples 1 and 2, the change in cell volume after 8 weeks of storage was less than 0.2 mL, which was significantly lower than that of the cells using the positive electrode active material powders according to Comparative Examples 1 and 2. This indicates that the high temperature storage characteristics of the battery are improved when the positive electrode active material powder according to the present invention is used.
[0125] Experimental Example 4 Monocells including positive and negative electrodes were fabricated. The positive electrodes were fabricated by coating the positive active material powders fabricated in Examples 1-2 and Comparative Examples 1-2 on a current collector and drying. The negative electrodes were fabricated by mixing natural graphite and artificial graphite in a ratio of 5:5 to use as the negative active material, and the negative electrodes were fabricated with a ratio of 95.6 wt% negative active material, 0.9 wt% conductive material, and 3.4 wt% binder. The loading of the negative electrodes was 10.7 mg / cm. 2 The N / P ratio of the negative electrode and the positive electrode was fixed at 1.08.
[0126] The capacity retention rates (%) of the mono-cells containing the positive electrode active material powders of Examples 1 and 2 and Comparative Examples 1 and 2 were measured at a temperature of 45° C. for 300 cycles, and the results are shown in FIG.
[0127] 6, it can be seen that the capacity retention rate of the mono-cell using the positive electrode active material powders of Examples 1 and 2 under the 300 cycle condition is 92% or more, whereas the capacity retention rates of the mono-cell using the positive electrode active material powders of Comparative Examples 1 and 2 are at the level of 87% and 85%, respectively. In other words, it can be seen that the high-temperature life characteristics are improved when the positive electrode active material powder according to the present invention is used.
[0128] Experimental Example 5 - Initial Resistance Measurement Coin half cells containing the positive electrode active material powders of Examples 1 and 2 and Comparative Examples 1 and 2 were manufactured, and the initial resistance values were measured. st Based on cycle discharge capacity, 2 nd After setting the SOC at 10% at 0.2C in the cycle, the voltage change rate was calculated when a current of 1C was applied for 60 seconds.
[0129] The initial resistance values for Examples 1 and 2 and Comparative Examples 1 and 2 are shown in Table 2 below.
[0130] [Table 2]
[0131] Referring to the results in Table 2, when the positive electrode active material powders of Examples 1 and 2 were used, the initial resistance value based on SOC.10% was measured to be lower than when the positive electrode active material powders of Comparative Examples 1 and 2 were used. This confirms that when the positive electrode active material powder according to the present invention is used in a battery, the initial resistance characteristics are improved.
Claims
1. The lithium transition metal composite oxide has at least one form of a single particle consisting of one nodule and a quasi-single particle which is a composite of 30 or less nodules, A positive electrode active material powder for a lithium secondary battery that satisfies the following formula 1: [Formula 1] 0.5≦D mean ×d press / D 50 ≦3 The above D mean is the average particle size of the nodules measured by electron backscatter diffraction (EBSD), The above d press is a press density value measured after 5 g of the positive electrode active material powder is placed in a circular mold having a diameter of 2 cm and then pressurized at 2000 kgf, The above D 50 is a 50% volume cumulative distribution value of the positive electrode active material powder, The d press is between 3 and 3.5 g / cc.
2. The lithium composite transition metal oxide has a composition represented by the following Chemical Formula 1: [Chemical formula 1] Li 1+x Ni a Co b M 1 c M 2 d O 2 In the above Chemical Formula 1, M 1 is Mn, Al or a combination thereof, M 2 is one or more selected from the group consisting of W, Zr, Y, Ba, Ca, Ti, Mg, Ta, and Nb, and 0≦x≦0.5, 0.8≦a<1, 0<b<0.2, 0<c<0.2, and 0≦d≦0.
05.
3. 3. The positive electrode active material powder for a lithium secondary battery according to claim 2, wherein in Chemical Formula 1, 0.82≦a≦0.
95.
4. The positive electrode active material powder for a lithium secondary battery according to claim 1, wherein the positive electrode active material powder has a full width at half maximum change rate of a (003) peak represented by the following formula 2 of 25% or less: [Formula 2] (003) peak full width at half maximum change rate=[{(003) peak full width at half maximum at SOC. 60%−(003) peak full width at half maximum at SOC. 0%} / {(003) peak full width at half maximum at SOC. 0%}]×100
5. 5. The positive electrode active material powder for lithium secondary batteries according to claim 4, wherein a rate of change of full width at half maximum of a (003) peak of the positive electrode active material powder is 15% or less.
6. The above D mean The positive electrode active material powder for lithium secondary batteries according to claim 1, wherein the particle size is 0.5 to 3.5 μm.
7. 2. The positive electrode active material powder for lithium secondary batteries according to claim 1, further comprising a coating layer disposed on a surface of the lithium composite transition metal oxide particles having at least one of the form of single particles and quasi-single particles, the coating layer including one or more coating elements selected from the group consisting of Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mo, Sr, Sb, Bi, Si, and S.
8. The positive electrode active material powder has a BET specific surface area of 0.1 m 2 / g to 1m 2 The positive electrode active material powder for a lithium secondary battery according to claim 1, wherein the powder has a molecular weight of 1000 or more and a molecular weight of 1000 or more.
9. A positive electrode for a lithium secondary battery comprising the positive electrode active material powder according to any one of claims 1 to 8.
10. A lithium secondary battery comprising the positive electrode according to claim 9.
Citation Information
Patent Citations
Cathode active material, method of producing the same, and cathode and lithium secondary battery employing the same
JP2015018803A